High Gain Non Isolated DC-DC Step-up Converters Integrated with Active and Passive Switched Inductor Networks - M. Al Mamun; Golam Sarowar; Md. Ashraful Hoque; Mehedi Azad Shawon (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
High gain dc-dc step up converters have been used in renewable energy systems, for example, photovoltaic grid connected system and fuel cell power plant to step up the low level dc voltage to a high level dc bus voltage. If the conventional boost converter is to meet this demand, it should be operated at an extreme duty cycle (duty cycle closes to unity), which will cause electromagnetic interference, reverse recovery problem and conduction loss at the power switches. This paper proposes a class of non-isolated dc-dc step up converters which provide very high voltage gain at a small duty cycle (duty cycle < 0.5). Firstly, the converter topologies are derived based on active switched inductor network and combination of active and passive switched inductor networks; secondly, the modes of operation of proposed active switched inductor converter and combined active and passive switched inductor converter are illustrated; thirdly, the performance of the proposed converters are analyzed mathematically in details and compared with conventional boost converter. Finally, the analysis is verified by simulation results.